2021
DOI: 10.1128/aac.02412-20
|View full text |Cite
|
Sign up to set email alerts
|

Trade-Offs between Antibacterial Resistance and Fitness Cost in the Production of Metallo-β-Lactamases by Enteric Bacteria Manifest as Sporadic Emergence of Carbapenem Resistance in a Clinical Setting

Abstract: Meropenem is a clinically important antibacterial reserved for treatment of multi-resistant infections. In meropenem-resistant bacteria of the family Enterobacterales, NDM-1 is considerably more common than IMP-1, despite both metallo-β-lactamases (MBLs) hydrolysing meropenem with almost identical kinetics. We show that blaNDM-1 consistently confers meropenem resistance in wild-type Enterobacterales, but blaIMP-1 does not. The reason is higher blaNDM-1 expression because of its stronger promoter. However, the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 44 publications
(43 reference statements)
0
7
0
Order By: Relevance
“…By contrast, a greater number of ESBL resistance genes were detected post incubation than direct from water filter. There has been an increase in data surrounding the relative fitness costs on bacteria that harbour resistance markers in the absence of selection pressure, notably those associated with large mobile plasmids (Cheung et al, 2021; Huang et al, 2013; Melnyk et al, 2015). We hypothesise that the loss here is due to carbapenemases being less stable within bacteria than ESBLs, similar to outcomes observed by Cheung et al, (2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, a greater number of ESBL resistance genes were detected post incubation than direct from water filter. There has been an increase in data surrounding the relative fitness costs on bacteria that harbour resistance markers in the absence of selection pressure, notably those associated with large mobile plasmids (Cheung et al, 2021; Huang et al, 2013; Melnyk et al, 2015). We hypothesise that the loss here is due to carbapenemases being less stable within bacteria than ESBLs, similar to outcomes observed by Cheung et al, (2021).…”
Section: Discussionmentioning
confidence: 99%
“…There has been an increase in data surrounding the relative fitness costs on bacteria that harbour resistance markers in the absence of selection pressure, notably those associated with large mobile plasmids (Cheung et al, 2021; Huang et al, 2013; Melnyk et al, 2015). We hypothesise that the loss here is due to carbapenemases being less stable within bacteria than ESBLs, similar to outcomes observed by Cheung et al, (2021). However, more extensive research is needed to both further our understanding of AMR as well as guide laboratory practice.…”
Section: Discussionmentioning
confidence: 99%
“…NDM-1 is more prevalent than IMP-1 in carbapenem-resistant Enterobacterales despite exhibiting similar activities in vitro (15,17). Avison and coworkers (84) have shown that this is due to higher expression levels of NDM-1, since the blaNDM-1 gene is found downstream an ISAba125 insertion sequence which provides a conserved strong promoter. In contrast, blaIMP-1 genes are located downstream of variable promoter sequences with different strengths, resulting in lower protein levels and, consequently, reduced resistance (84).…”
Section: Evolution Of Mbls In Different Bacterial Hosts: Genetic and Biochemical Determinants Of Specificitymentioning
confidence: 99%
“…Avison and coworkers (84) have shown that this is due to higher expression levels of NDM-1, since the blaNDM-1 gene is found downstream an ISAba125 insertion sequence which provides a conserved strong promoter. In contrast, blaIMP-1 genes are located downstream of variable promoter sequences with different strengths, resulting in lower protein levels and, consequently, reduced resistance (84). An E. coli isolate carrying the blaIMP-6 gene was shown to be susceptible to imipenem and meropenem, as the result of the transcriptional repression of blaIMP-6.…”
Section: Evolution Of Mbls In Different Bacterial Hosts: Genetic and Biochemical Determinants Of Specificitymentioning
confidence: 99%
See 1 more Smart Citation